An Audit System Causality Model for Construction Safety Management System Assessment in Building Projects using Integrated Design-Build - Arifuddin, Rosmariani; Latief, Yusuf; Wibowo, Mochamad Agung; Nugroho, Danang Budi; Alfawaid, Ahmad Bakir; Fadlillah, Muh Rifan (Engineering, Technology & Applied Science Research, 2025)
Increasing the implementation of Construction Safety Management Systems (CSMSs) has proven to be an effective strategy for preventing construction accidents. Unfortunately, the current safety audit system is still not fully developed at each stage of the project life cycle, especially in integrated design-build contracts for construction projects. Based on this phenomenon, the objectives of the current research were developed, which include identifying the indicators and sub-indicators of the performance assessment audit system, and designing a causality model of the indicators and sub-indicators of the assessment audit system in each project life cycle, especially for the integrated design-build contract. The research method comprises a literature review and expert validation to obtain the indicators and sub-indicators for the safety system audit. In addition, a perception survey was conducted through with questionnaires being distributed to safety engineers and safety personnel in several construction projects. The questionnaire data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to develop a causality model for the safety indicators and sub-indicators. The study results obtained five indicators and eighty-six sub-indicators in the safety audit system that significantly influenced the performance of safety implementation in construction projects. Moreover, he causality model obtained Y1 = 0.2518X1 - 0.0308X2 - 0.3523X3 + 0.4188X4 - 0.0693X5 including: X1 leadership and worker participation in construction safety, X2 construction safety planning, X3 construction safety support, X4 construction safety operational, and X5 construction safety performance evaluation. The results of this study are expected to act as a reference, especially for service providers implementing the elements of the audit system.